Whole Transcriptome Mapping Identifies an Immune- and Metabolism-Related Non-coding RNA Landscape Remodeled by Mechanical Stress in IL-1β-Induced Rat OA-like Chondrocytes - Zhang, Jiaming; Hao, Xiaoxia; Chi, Ruimin; Liu, Jiawei; Shang, Xingru; Deng, Xiaofeng; Qi, Jun; Xu, Tao (Frontiers in Genetics, 2022)
Background: Osteoarthritis (OA) is a common degenerative joint disease. This study is aimed to explore the effects of mechanical stress on whole transcriptome landscape and to identify a non-coding transcriptome signature of mechanical stress. Methods: Next-generation RNA sequencing (RNA-seq) was performed on IL-1β-induced OA-like chondrocytes stimulated by mechanical stress. Integrated bioinformatics analysis was performed and further verified by experimental validations. Results: A total of 5022 differentially-expressed mRNAs (DEMs), 88 miRNAs (DEMIs), 1259 lncRNAs (DELs), and 393 circRNAs (DECs) were identified as the transcriptome response to mechanical stress. The functional annotation of the DEMs revealed the effects of mechanical stress on chondrocyte biology, ranging from cell fate, metabolism, and motility to endocrine, immune response, and signaling transduction. Among the DELs, ~92.6% were identified as the novel lncRNAs. According to the co-expressing DEMs potentially regulated by the responsive DELs, we found that these DELs were involved in the modification of immune and metabolism. Moreover, immune- and metabolism-relevant DELs exhibited a notable involvement in the competing endogenous RNA (ceRNA) regulation networks. Silencing lncRNA TCONS_00029778 attenuated cellular senescence induced by mechanical stress. Moreover, the expression of Cd80 was elevated by mechanical stress, which was recused by silencing TCONS_00029778. Conclusion: The transcriptome landscape of IL-1β-induced OA-like chondrocytes was remarkably remodeled by mechanical stress. This study identified an immune- and metabolism-related ncRNA transcriptome signature responsive to mechanical stress and provides an insight of ncRNAs into chondrocyte biology and OA.